Studi Alur Pengadaan Barang dan Jasa (Studi kasus: Perum PNRI) - Timothy Lorenzo Manik; Muhamad Taufiq Rachmat; Apid Hapid Maksum (Jurnal Serambi Engineering, 2023)
Procurement management in a state-owned enterprise refers to acquiring goods or services or works from external suppliers. The goal of procurement in a state-owned enterprise is to ensure that the company obtains the goods, services, or works it needs in a cost-effective and efficient manner. By optaining supplies from vendors, many benefit would be received to company. For example, high quality goods or services, growth of efficiency, chance of competitiveness in market and many more. In this research, the main object is to identify flow of direct appointment and direct election and vendor performance evaluation of procurement goods and services in Perum Percetakan Negara RI. As for the flow of these methods are similar which are Request for procurement of goods or services, Preparation for procurement goods or services, Procurement process of goods or services, Determination or proposal, Approval letter, Contract sign, Delivery of goods or services and handover. In the process of procurement, work order is issued, in which issued by department of Procurement.